ANALISIS PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN DI PT. INDONESIA EPSON INDUSTRY - Amelia, Fitria; Sadli, Andi Muhammad; Surtini (Mulia Pratama, 2024)
This study aims to determine the effect of compensation and work environment on employee performance. This research is quantitative with a population of 37 people and a sample of 37 people. The primary data collection method was carried out using observation methods and questionnaires as data collection instruments. To measure the research variables, a Likert scale measurement with five scales was used. While the analysis tool is multiple linear regression analysis. The results of the analysis show that employee performance is influenced by compensation and the work environment, both partially and simultaneously. For this reason, it is suggested that PT. Indonesia Epson Industry always pays attention to these two factors in order to improve employee performance.